An Example of Gender Construction of Children From Different Socio‐Economic Levels Through the Phenomenon of Parenting. - Kurt, Şerife Hülya (Child & Family Social Work, 2026)
This study examined the transmission of gender within the family through perceptions of parenting in low‐ and middle‐income families. Phenomenology design, one of the qualitative research methods, was used in the study. Participants were determined by criterion sampling method. Data were collected from 60 participants, including 20 families (mother–father–child) representing low (10 families) and middle (10 families) socio‐economic levels. The study reveals that there is a need for social intervention in both socio‐economic contexts. The findings of the study showed that the gendered interactions of parents living in both socio‐economic contexts within the family had effects on children's perceptions and experiences. In the study, parents in both socio‐economic contexts characterized motherhood as sacrifice, caregiving, and fertility and fatherhood as authority, power, income, and security provider. Children, on the other hand, defined motherhood as providing care, fertility, and being responsible for household chores and fatherhood as providing income, meeting needs, and having a profession. A striking result of the study is that although both parents were employed, children preferred to use expressions related to the fathers' professional life while defining parenthood.